Returns to Investment in Education : A Decennial Review of the Global Literature - Psacharopoulos, George; Patrinos, Harry Anthony (World Bank, Washington, DC, 2018)
Returns to investment in education based on human capital theory have been estimated systematically since the 1950s. In the 60-plus year history of such estimates, there have been several compilations in the literature. This paper reviews and highlights the latest trends and patterns based on a database of 1,120 estimates in 139 countries. The review shows that the private average global rate of return to one extra year of schooling is about 9 percent a year and very stable over decades. Private returns to higher education have increased over time, raising issues of financing and equity. Social returns to schooling remain high, above 10 percent at the secondary and higher education levels. Women continue to experience higher average rates of return to schooling, showing that girls' education remains a priority. Returns are higher in low-income countries. Those employed in the private sector of the economy enjoy higher returns than those in the public sector, lending support to the productive value of education.